2006
DOI: 10.1016/j.neuroscience.2006.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Histometric changes and cell death in the thalamus after neonatal neocortical injury in the rat

Abstract: Freezing injury to the developing cortical plate results in a neocortical malformation resembling four-layered microgyria. Previous work has demonstrated that following freezing injury to the somatosensory cortex, males (but not females) have more small and fewer large cells in the medial geniculate nucleus. In the first experiment, we examined the effects of induced microgyria to the somatosensory cortex on neuronal numbers, neuronal size, and nuclear volume of three sensory nuclei: ventrobasal complex, dorsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 69 publications
4
16
0
Order By: Relevance
“…These findings are consistent with both clinical observations and rodent models of injury-induced and genetic models of MCD, where impairments in RAP, coupled with a shift in neuronal size distribution toward more small neurons in the MGN, have both been reported relative to controls [36,[48][49][50]52]. Although the present results further support a link between MCD, impaired auditory processing, and alterations in MGN morphology, the precise neural underpinnings of the deficient auditory phenotype as well as the etiology of the thalamic alterations remain unclear.…”
Section: MCD Neuronal Size Changes In the Mgn And Rapid Auditory Prsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings are consistent with both clinical observations and rodent models of injury-induced and genetic models of MCD, where impairments in RAP, coupled with a shift in neuronal size distribution toward more small neurons in the MGN, have both been reported relative to controls [36,[48][49][50]52]. Although the present results further support a link between MCD, impaired auditory processing, and alterations in MGN morphology, the precise neural underpinnings of the deficient auditory phenotype as well as the etiology of the thalamic alterations remain unclear.…”
Section: MCD Neuronal Size Changes In the Mgn And Rapid Auditory Prsupporting
confidence: 89%
“…Male rats with injury-induced cerebrocortical microgyria (comparable in structure to those found in dyslexic individuals studied by Galaburda et al) also showed impairments in RAP [45][46][47]. Subsequent examination of neuronal size in the MGN of male rats with injury-induced microgyria revealed not only smaller neurons in general, but a shift in the distribution of neuronal sizes toward the left (smaller neurons) compared to sham controls [48][49][50]. Genetic knockdown of the rodent homolog Dyx1c1-a candidate dyslexia risk gene in humans-also have been shown to lead to MCD (e.g., neural ectopias in layer 1 of the cortex, white matter heterotopia; [51][52][53]).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…The two pathways may also have distinct developmental sensitivity. Early developmental perturbations alter frequency bandwidth (and resolution) in VAF moreso than in A1, and the effect may ultimately be traced back to developmental change in thalamocortical pathways (Escabi et al, 2007;Higgins et al, 2008;Rosen et al, 2006). Future studies will be needed to determine whether a VAF-specific loss of frequency resolution is associated with pathway-specific restructuring of the MGBv frequency organization described here.…”
Section: Discussionmentioning
confidence: 91%
“…Excitotoxicity and inflammation leading to neuronal cell death can extend from days to weeks following perinatal brain damage (Ferriero, 2004, Hagberg, et al, 2002, Rosen, et al, 2006, Volpe, 2008, Volpe, 2009). Elevated pro-inflammatory cytokines are major contributors to the onset of inflammation in neonatal HI injury, which may cause and/or accentuate neuronal pathology predisposing neonates to poor neurobehavioral outcomes (Grether, et al, 2003, Leviton, et al, 2011, Nelson, et al, 1998, Szaflarski, et al, 1995, Yoon, et al, 1997, Yoon, et al, 1997, Yoon, et al, 1997).…”
Section: Introductionmentioning
confidence: 99%